Development of a tissue-specific prodrug activation approach to prostate cancer gene therapy - Foley, Ruth Elizabeth Louise (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2006)
Prostate cancer is the most common fatal cancer in Irish men after lung and colorectal cancer. Since the risk of prostate cancer rises with age, its impact is likely to increase as the population ages. Standard treatments fail to prevent disease progression in some patients, particularly those with advanced disease, and many novel therapies are therefore being investigated. Gene therapy is emerging as a promising adjuvant to conventional treatments. Several Phase I clinical trials have been carried out with generally acceptable safety profiles and evidence in some cases of biological activity against prostate cancer.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin